PENINGKATAN KEMAMPUAN KONEKSI MATEMATIK DAN SIKAP POSITIF SISWA DENGAN PEMBELAJARAN KONTEKSTUAL PADA SISWA SMK PELAYARAN SAMUDERA INDONESIA MEDAN - Taruli Marito Silalahi (MES: Journal of Mathematics Education and Science, 2018)
Abstract. This research aimed study to determine: 1) the increasing ability of mathematic connection and student’s positive thingking by using Contextual Learning are higher than students or usual learning approach. 2) there was the interaction between learning by students mathematic ability toward the increasing ability of mathematic connection and student’s positive thinking. 3) to determine how the answering process are made by the students in problem solving by using contextual learning and usual learning approach. This kind of research is the quasi experiment. The populations of this research are all of the students in X grade of Tehnical High School with acreditation B where is in Medan and the sample is chosen random sample. Where SMK Medan consist of X Nautic as experiment class and X Tehnical as control class am each consist of 34 students. The instrument used consist of: (1) test students initial mathematic ability, (2) test for mathematic connection and (3) scale for positive thingking, the subject up space. Data analysis are done by using ANAVA two ways. The result of this research shown that (1) the increasing ability in mathematic connection and student’s positive thinking by using Contextual Learning is higher than using student’s usual thinking approach, (2) there were no interaction between learning and student’s ability level to the increasing ability of mathematics and student’s positive thinking. The researcher suggests to use the Contextual Learning as the alternative way for teachers to increase the ability of mathematic connection and student’s positive thingking.Keyword: Contextual Learning, Mathematical Connection Ability, and Positive Student Attitudes